2021
DOI: 10.4018/ijssmet.20220301.oa1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on the GCC Construction Industry

Abstract: The Coronavirus pandemic has badly affected everyone on the earth. Apart from losing thousands of lives, businesses and individuals are going to be affected by the long-lasting financial effects due to an expected global recession. The impact of the financial crises can, however, be reduced if proper measured are put in place. This article aims to investigate the impact of Coronavirus on the construction industry in the Gulf Cooperation Council (GCC) member countries and provide recommendations to help the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 30 publications
0
36
0
1
Order By: Relevance
“…Hussain et al (2019) describes that adoption of research methodology to classify the best findings for study is a significant task. Umar (2022) identified that two elements including specific research questions and investigation of specific topic while reviewing the research technique are very important for researchers to encounter the research methodologies. Jobber et al (1991) identified that supporting of one methodology on the basis of some advantages is totally wrong because every methodology has some pros and cons.…”
Section: Methodsmentioning
confidence: 99%
“…Hussain et al (2019) describes that adoption of research methodology to classify the best findings for study is a significant task. Umar (2022) identified that two elements including specific research questions and investigation of specific topic while reviewing the research technique are very important for researchers to encounter the research methodologies. Jobber et al (1991) identified that supporting of one methodology on the basis of some advantages is totally wrong because every methodology has some pros and cons.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire was developed based on the previous similar studies. The researcher depended on (Rehman et al, 2021;Ogunnusi et al, 2021;Ayat-Kang, 2021;Umar, 2022;Walker, 2015;Heagney, 2016;White-Fortune, 2002;Cleland, 2007;Picciotto, 2020;Larsson-Larsson, 2020;San Cristóbal et al, 2018;Borkovskaya, 2018;Mavi-Standing, 2018;Jugdev et al, 2019) in building the questionnaire.…”
Section: Study Toolmentioning
confidence: 99%
“…Source: Based on Ayat & Kang (2021), Umar (2022), Cleland (2007), Picciotto (2020) Also, the results show that the paragraph "There is an impact of the Corona pandemic on discovering errors during the implementation process" has the highest approval by the sample members by (4.2), The results show that the Corona pandemic has affected the process of discovering errors during the project implementation process, and this impact can be more negative than positive, as the pandemic may have reduced the control roles through the absence of some employees specialized in oversight, or through laws that forced Companies to condone some practices that workers may perform, such as absence from work due to quarantine requirements or absence due to illness.…”
Section: Total Mean 375mentioning
confidence: 99%
“…Productivity problems are experienced throughout the entire supply chain, with many projects relying on materials from overseas. COVID-19 has reduced the productivity of construction workers since its inception (Boamah et al, 2022;Umar, 2022). Furthermore, in terms of construction organisation resilience, Chih et al (2022) suggested short and long-term planning for all eventualities.…”
Section: The Impact Of Covid-19 On Construction Planning and Producti...mentioning
confidence: 99%